Concentration, ozone formation potential and source analysis of volatile organic compounds (VOCs) in a thermal power station centralized area: A study in Shuozhou, China. (April 2017) - Yan, Yulong; Peng, Lin; Li, Rumei; Li, Yinghui; Li, Lijuan; Bai, Huiling
Abstract: Volatile organic compounds (VOCs) from two sampling sites (HB and XB) in a power station centralized area, in Shuozhou city, China, were sampled by stainless steel canisters and measured by gas chromatography-mass selective detection/flame ionization detection (GC-MSD/FID) in the spring and autumn of 2014. The concentration of VOCs was higher in the autumn (HB, 96.87 μg/m 3 ; XB, 58.94 μg/m 3 ) than in the spring (HB, 41.49 μg/m 3 ; XB, 43.46 μg/m 3 ), as lower wind speed in the autumn could lead to pollutant accumulation, especially at HB, which is a new urban area surrounded by residential areas and a transportation hub. Alkanes were the dominant group at both HB and XB in both sampling periods, but the contribution of aromatic pollutants at HB in the autumn was much higher than that of the other alkanes (11.16–19.55%). Compared to other cities, BTEX pollution in Shuozhou was among the lowest levels in the world. Because of the high levels of aromatic pollutants, the ozone formation potential increased significantly at HB in the autumn. Using the ratio analyses to identify the age of the air masses and analyze the sources, the results showed that the atmospheric VOCs at XB were strongly influenced by the remote sources of coal combustion, while at HB in the spring and autumn were affected by the remote sources of coal combustion and local sources of vehicle emission, respectively. Source analysis conducted using the Positive Matrix Factorization (PMF) model at Shuozhou showed that coal combustion and vehicle emissions made the two largest contributions (29.98% and 21.25%, respectively) to atmospheric VOCs. With further economic restructuring, the influence of vehicle emissions on the air quality should become more significant, indicating that controlling vehicle emissions is key to reducing the air pollution. Highlights: The level of VOCs was higher in autumn than spring, due to less wind speed in autumn could lead pollutant accumulated. Though sampling in a thermal power station centralized area, the pollution of BTEX was at low level. The influence of the remote source of coal combustion on atmospheric VOCs was higher than local source of vehicle emission. With further economic restructuring, the influence of vehicle emissions on the air quality should become more significant, indicating that controlling vehicle emissions is key to reducing the air pollution. Abstract : Though coal combustion from power generation was the main source of VOCs, vehicle emissions have become an important source in the thermal power station centralized area.